Development and in vitro bioevaluation of cockle shell-calcium carbonate (Aragonite) nanoparticles for intracellular drug delivery - Isa, Tijani (2015)
The use of safe and efficient delivery systems, capable of delivering therapeutic agents to subcellular levels are an ultimate goal in enhancing therapeutic effect. It is also a promising strategy in overcoming microbial resistance and the emergence of intracellular bacterial infections. The challenge, however, is that the interaction of nanoparticles with biological systems at the cellular level must be established prior to biomedical applications. In this study,ciprofloxacin conjugated cockle shells-derived calcium carbonate (aragonite) nanoparticle (CCSCCAN) was developed and characterized for its physicochemical properties and antibacterial activities. Biocompatibilities were evaluated on macrophage cell line (J774.A1) using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and 5-Bromo-2ʹ-deoxyuridine (BrdU) assays. The nanoparticles were spherical in shape, with particles sizes ranging from 11.93 to 22.12 nm as determined through a transmission electron microscope (TEM). The highest percentage entrapment efficiency (EE) and loading content (LC) were 99.5% and 5.9%, respectively, with an optimum negative zeta potential. X-ray diffraction (XRD) patterns revealed strong crystallity of the formulations. Fourier transforms infrared (FT-IR) spectra shows evident of interactions exist between the drug and nanoparticles at the molecular level. No burst effect, but a sustained drug release was observed from the formulation. The mean diameter of inhibition zone was 18.6 ± 0.5 mm, which was better than ciprofloxacin alone (11.7 ± 0.9 mm), while the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the formulation were lower than those of free drugs. Study of biocompatability suggested non-toxic effects of the formulations. In conclusion, the results indicated that the ciprofloxacin- nanoparticle conjugate (C-CSCCAN) enhanced susceptibility of Salmonella and antibacterial efficacy of the antibiotic, which could potentially improve the clinical efficacy of the drug.